Role of pH on biological Nitrification Process - Amatya, Iswar Man; Kansakar, Bhagwan Ratna; Tare, Vinod; Fiksdal, Liv (Journal of the Institute of Engineering, 2011)
It is important to determine the effect of changing environmental conditions on the microbial kinetics for design and modeling of biological treatment processes. In this research, the kinetics of ammonia oxidation by nitrifying process bacteria under varying pH and temperature conditions are studied. Ammonia oxidation in groundwater was carried out by biological method of nitrification process. The nitrification was performed in one set of reactors. The reactor consists of two columns connected in series packed with over burnt bricks as media. The filtration rate varied from 10.5 to 210.4 m/day for nitrification process respectively. The ammonia, nitrate and nitrite nitrogen concentrations were measured at inlet, intermediate ports and outlet. The temperature varied from 10 to 30°C at 2°C intervals. The results demonstrated that high amounts of ammonia nitrogen nitrified in groundwater at nitrification process. The average ammonia nitrogen oxidation efficiency of 77.27% was achieved from pH 7.3 to 8.0 in the reactor packed with OBB media at 20°C, for the flow rate 500ml/min due to biological nitrification. The total amount of ammonia nitrogen removed by nitrification varied from 0.76 to 17.80 gm/m3/h at influent concentration from 2.84 to 149.28 gm/m3/h. Key words: Over burnt brick; Filtration rate; Temperature; Nitrification and Nitrifying bacteria DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5102 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 119-125 Uploaded Date: 20 July, 2011